Brexit: what are the options for the financial services industry?. Issue 4 (7th November 2016) - Sahr, David; Compton, Mark; Carr, Alexandria; Wilkes, Guy; Behrens, Alexander
Abstract : Purpose: To explain the impact for financial services firms of the UK's vote to leave the European Union (EU) and to assess the possible options for conducting cross-border financial services between the UK and EU in the future. Key to this is the likely loss of the EU "passport" for financial services that allows a firm licensed in one EU state to offer its services freely throughout all EU states. Design/methodology/approach: Explains the process by which the UK will leave the EU and negotiate future trading arrangements; the key considerations for financial services firms doing cross-border business in the EU; the various options for cross-border business in the future; and the key steps financial services firms should be taking to respond to the vote to leave the EU. Findings: Many issues still remain uncertain and are unlikely to be resolved for a number of years, but long lead times to implement solutions mean that firms should be considering their options now. Practical implications: Firms should be evaluating their current reliance on EU passports and the alternative options that might be suited to their business, such as the "quasi-passports" available under certain specific EU laws or relocation of part or all of their business. Originality/value: Legal analysis and practical guidance concerning an unprecedented political development with profound impacts on financial services in Europe, by experts with long-term experience of EU negotiations and financial services gained from working for the British government, regulators and regulated firms.